Data associated with “Third Body Damage and Wear in Arthroplasty Bearing Materials: A Review of Laboratory Methods” - Cowie, Raelene; Jennings, Louise (University of Leeds, 2021)
The dataset contains material to supplement the review paper “Third Body Damage and Wear in Arthroplasty Bearing Materials: A Review of Laboratory Methods” including: tables summarising papers and abstracts reviewed in the article and data relating to figures for the methods used for simulating third body wear, the types of third body particles used and the particle diameter.
Keywords: FOS: Medical engineering